FREQUENCY OF OTITIS MEDIA IN PATIENTS OF NASAL POLYPI - Chaudhry, Sadia; Ahmad, Zafar; Khan, Faraz Basharat; Afzal, Mohammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Otitis media is a common disease encountered in ENT practice. Its incidence has fallen in the developed world. It is expected that nasal polypi causes Eustachian tube dysfunction which in turn leads to negative middle ear pressure causing to develop otitis media with effusion or recurrent otitis media. The objective of this study was to find the frequency of Otitis Media in patients of nasal polypi. Subjects and Methods: It was a cross-sectional study. Seventy patients with bilateral nasal polypi were taken for study from OPD of ENT Department, Fauji Foundation Hospital Rawalpindi. Purposive (non-probability) sampling was done keeping p=4%. There were 24 (34.3%) males and 46 (65.7%) females included in the study. Age range was 26-38 years. Tympanometry was done in every patient to look for signs of Otitis media. Duration of study was from 24th Apr 2008 to 30th Jul 2009. Results: In our study, all patients were having bilateral nasal polypi. Age range was between 26 and 38 years. Frequency of patients having retracted tympanic membrane on right side was 25 (35.7%), and those who developed it on left side was 30 (42.9%). However, 35 (50%) of the 70 patients were having retraction of tympanic membrane whether right or left. This shows frequency of otitis media in patients of nasal polypi was found to be 50%. Conclusion: Frequency of developing otitis media in patients of nasal polypi is quite high. Nasal problems lead to development of ear diseases. Keywords: Otitis Media, Nasal Polyp, Middle Ear, Eustachian Tube, Tympanometry